2011
DOI: 10.1002/oti.319
|View full text |Cite
|
Sign up to set email alerts
|

Working Conditions of Occupational Therapists in Jordan

Abstract: The purpose of this study was to investigate the working conditions and factors related to job satisfaction among Jordanian occupational therapists. A self-administered survey consisting of several questions about the participants' jobs was developed for this study. The inclusion criteria included occupational therapists who worked in the field of occupational therapy (OT) in Jordan and who had at least six months of experience. The survey was distributed to 120 occupational therapists in different OT settings… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…In Jordan and the Levant area, there is a dearth of standardized assessment tools that are culturally valid and can be used for clinical and research purposes with the Jordanian population, in part due to the fact that OT profession in Jordan is still young (Abu‐Tariah et al . ). The limited number of assessment tools has a major effect on evaluation, intervention planning and intervention among Jordanian occupational therapists, and is a major professional concern (Abu‐Tariah et al .…”
mentioning
confidence: 97%
“…In Jordan and the Levant area, there is a dearth of standardized assessment tools that are culturally valid and can be used for clinical and research purposes with the Jordanian population, in part due to the fact that OT profession in Jordan is still young (Abu‐Tariah et al . ). The limited number of assessment tools has a major effect on evaluation, intervention planning and intervention among Jordanian occupational therapists, and is a major professional concern (Abu‐Tariah et al .…”
mentioning
confidence: 97%
“…The results of our study revealed that current practising occupational therapists in Beijing are relatively young and less experienced as compared with therapists from countries with more established OT professions, for example the United States, Sweden and Singapore (Yang et al, 2006;Karlsson and Tornquist, 2007;AOTA, 2010). More than half of the participants in this study were younger than 30 and had less than 5 years of (Tariah et al, 2011a;Chen et al, 2012). It is hoped that this phenomenon will improve with time.…”
Section: Discussionmentioning
confidence: 73%
“…More than half of the participants in this study were younger than 30 and had less than 5 years of experience working as an occupational therapist. Countries with newly developed OT professions, such as Jordan and Malaysia, reported similar phenomena (Tariah et al ., ; Chen et al ., ). It is hoped that this phenomenon will improve with time.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…This non-evidence strategy to address shortage of health professionals for rehabilitative services, aggravates a medical governance system that stifles further development of the profession. In short, occupational therapists in developed countries have enjoyed significant advancement, job autonomy and job recognition [25], but not those from developing countries [26,27].…”
mentioning
confidence: 99%